2021
DOI: 10.1111/raq.12581
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by dietary supplements: A preventive health strategy for sustainable aquaculture of tropical freshwater fish, Labeo rohita (Hamilton, 1822)

Abstract: Dietary supplementation is an effective strategy for boosting the innate immune response in fishes. It involves the use of functional ingredients that bear the potential for mitigating the deleterious effects of chemotherapeutics (bioaccumulation and development of drug-resistant pathogens), as a more ecologically responsible approach to fish farming. With the emergence of probiotics, prebiotics, synbiotics and herbal immunostimulants; dietary supplementation has become an integral aspect of immunonutrition. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 162 publications
0
5
0
Order By: Relevance
“…Sustainably preventing aquaculture diseases is desirable, but not always possible since supplying the optimal conditions and feeding can be economically challenging. Furthermore, its success may require effective biocontrol techniques to reduce infections [ 97 , 98 ]. The rapid spread and the ubiquitous nature of fish pathogenic microorganisms mean that infection control and prevention can be difficult [ 99 , 100 ].…”
Section: Disease Control and Alternative Approachesmentioning
confidence: 99%
“…Sustainably preventing aquaculture diseases is desirable, but not always possible since supplying the optimal conditions and feeding can be economically challenging. Furthermore, its success may require effective biocontrol techniques to reduce infections [ 97 , 98 ]. The rapid spread and the ubiquitous nature of fish pathogenic microorganisms mean that infection control and prevention can be difficult [ 99 , 100 ].…”
Section: Disease Control and Alternative Approachesmentioning
confidence: 99%
“…Glucans play a very important role in aquaculture as immunostimulant to improve the performance and health of farmed animals. β-Glucan has been found to induce immunity in various cultured fish species and resistance against different pathogens has been reported ( 8 , 37 , 38 ). Research have shown that β-glucan dosages, quality, route, and time of administration and duration of treatments may influence the its beneficial effects on growth, survival, and immunity of fish ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oreochromis niloticus infected with A. hydrophila and fed a diet containing Withania sominefera extract showed increased lysozyme activity as well [81] . All of these findings suggested that plant extract supplementation diets can benefit fish with non-specific immune responses [82] .…”
Section: Discussionmentioning
confidence: 99%